Synthesis and Biological Evaluation of New Carbohydrate-Substituted Indenoisoquinoline Topoisomerase I Inhibitors and Improved Syntheses of the Experimental Anticancer Agents Indotecan (LMP400) and Indimitecan (LMP776) - Beck, Daniel E. (American Chemical Society, 2014)
[Image: see text] Carbohydrate moieties were strategically transported from the indolocarbazole topoisomerase I (Top1) inhibitor class to the indenoisoquinoline system in search of structurally novel and potent Top1 inhibitors. The syntheses and biological evaluation of 20 new indenoisoquinolines glycosylated with linear and cyclic sugar moieties are reported. Aromatic ring substitution with 2,3-dimethoxy-8,9-methylenedioxy or 3-nitro groups exerted strong effects on antiproliferative and Top1 inhibitory activities. While the length of the carbohydrate side chain clearly correlated with antiproliferative activity, the relationship between stereochemistry and biological activity was less clearly defined. Twelve of the new indenoisoquinolines exhibit Top1 inhibitory activity equal to or better than that of camptothecin. An advanced synthetic intermediate from this study was also used to efficiently prepare indotecan (LMP400) and indimitecan (LMP776), two anticancer agents currently under investigation in a Phase I clinical trial at the National Institutes of Health.